Hubungan Teknik Menyikat Gigi Pasien Ortho Cekat terhadap Kebersihan Gigi dan Mulut di Deneira Dental Clinic Jakarta Selatan - Pariati, Pariati; Dwi Rezky Aulyah; Faradillah Usman; Fidzah Nurfajrina Murad; Suciyati Sundu (Jurnal Siti Rufaidah, 2025)
Oral hygiene in fixed orthodontic patients is a significant challenge because the presence of brackets and archwires easily traps food debris, making it difficult to maintain dental health. A preliminary survey at Deneira Dental Clinic, South Jakarta, found that some patients using fixed orthodontics still have poor dental hygiene, characterized by debris and food residue adhering to the brackets. Interviews also revealed that most patients do not understand proper toothbrushing techniques for maintaining oral health. This study aimed to analyze the relationship between toothbrushing techniques and the oral hygiene status of fixed orthodontic patients at the clinic. Using a cross-sectional design involving 33 respondents through accidental sampling, data were collected using questionnaires and clinical examinations using the OHI-S index, then analyzed using the Chi-square test. The results showed that the majority of respondents using the combination toothbrushing technique had moderate oral hygiene, while in the roll technique group, the number of patients with moderate hygiene was also higher. These findings confirm that the toothbrushing technique used does not fully achieve optimal oral hygiene, although most patients still fall within the moderate category. Therefore, interventions in the form of comprehensive education from clinics regarding proper oral care methods, including the use of additional cleaning aids such as dental floss or mouthwash, are needed. Furthermore, patients are expected to be more consistent in maintaining daily oral hygiene. To strengthen these findings, further research is recommended exploring other factors, such as brushing frequency, toothbrush type, and diet, that may influence oral hygiene in orthodontic patients.